Distant Work with Students in Conditions of Social and Political Crisis - Kholod, Oleksandr (East European Journal of Psycholinguistics, 2015)
The aim of the study is to identify key features of distant study of students of a Kyiv University in the conditions of social and political crisis in Ukraine for the period from 1 to 25 December 2013. Among the identified features of the study are: i) as to the carrying out and submission of individual assignments, the Euromaidan events in Kyiv had a serious impact on the distant study; ii) due to the ambiguous students’ attitude to the events the individual assignments were multiple in nature; iii) the assessment of the quality of the submitted assignments was made according to the criteria described above being consistent with the nature and complexity of the tasks; iv) while commenting grades (according to the ECTS system) political and social orientation of students, as well as a measure of their participation in the events on Evromaydane; v) Despite the severity of the protests and political bias of students with motivation scores for remote job done, we had to admit honestly significant deficiencies that occur in the texts and procedures assignments. References Aysmontas, B. (2004). Nauchno-Metodicheskoe Obesprchenie Distantsionnoy Formy Podgotovki Psichologov [Scientific and Methodical Basis of Distant Form of Psychologist Training]. Retrieved from: http://ito.edu.ru/2006/ Moskva / III / 2 / III-2-6032.html. Andreyev, A. (1997). Vvedenie v Distantcionnoe Obuchenie [Introduction to Distant Learning]. Moscow: VU. Vishnevskaya, G. (2011). Vnedrenie distantsionnych tehnologii v protses obucheniya innostrannomu Yazyku Studentov-Zaochnikov Nejazykovvych Vuzov [Introduction of Distant Learning Technologies into Foreign Language Teaching of Non-Linguistic Part-time Students]. Izvestiya of V.Belinsky PGPU, 24 Retrieved from: http://cyberleninka.ru/članak/n/vnedreniedistantsionnyh-tehnologiy-v-protsess-obucheniya-inostran nomu-yazyku-Studentov-zaochnikovneyazykovyh-vuzov. Dmitriyeva, E. (1997). O perspektivach i voznoznostjach distantcionnogo obuchenija innostrannomu jazyku s ispolzovanirm telekomunikacionnych setej [On the prospects and possibilities of English language distant teaching by means of telecommunication networks]. Innostrannye Yazyki v Shkole, 2, 23–28. Karpenko, M. (2001). Distantsionnoe Obrazovanje kak Sovrenennoje Sredstvo Nepreryvnogo Obrazovanja [Distant Education as a Modern Means of Permanent Learning]. Moscow: MESI. Komrakov, E. (2004). Projektirovochnaja dejatelnost tjutora v sisteme otkrytogo distantsionnogo professionalnogo obrazovanja [Projective activity of tutor in the open system of distant professional education]. Ph.D. thesis. Moscow: Akademiya Povyscheniya Kvalifikatsii i Podgotovki Rabotnikov Obrazovanija Rossiyskoi Federatsii. Kreer, M. (2007). Ekspertnyj analiz kriterijev ocenki pismennoj rechi [Expert analysis of written discourse evaluation criteria]. Izvestija of A. Gertsen RGPU, 32, 322–326. Mekeko, N. (2008). Obuchenie Angliyskomu Yazyku Slushatelei Zaochnogo Otdelenija [English Learning by Part-time Students]. Moscow: AEB MVD. Polat E., Moses, M, Petrov, A. (2006). Pedagogicheskie Technologii Distantsionnogo Obuchenija [Pedagogical Technologies of Distant Education]. Moscow: Akademia. Soldatkin V.I. (1999). Problemy sozdanija i razvitija otkrytogo obrazovanija v Rosii [The issues of creating and developing open education in Russia]. Otkrytoje Obrazovanie, 5, 87. Hutorskoy, A. (2002). Distantsionnoe obuchenie i yego technologii [Distant teaching and its technologies]. Computerra, 36, 26–30. Hutorskoy, A. (2001). Nauchno-pakticheskie predposylki distantsionnoy pedagogiki [Scientific and methodical basis of distant form of psychologist training]. Otkrytoye Obrazovanie, 2, 30–35. Shennikov, S. (2003). Razvitiye sistemy otkrytogo distantsionnogo professionalnogo obrazovaniya [Development of open distant professional education system]. Ph.D. thesis. Moscow: Akademiya Povyscheniya Kvalifikatsii i Podgotovki Rabotnikov Obrazovanija Rossiyskoi Federatsii. 